PENGARUH PEMBERIAN TEPUNG TEMULAWAK DAN KUNYIT TERHADAP COOKING LOSS, DRIP LOSS DAN UJI KEBUSUKAN DAGING PUYUH JANTAN - Veronica Wanniatie; Dian Septinova; Tintin Kurtini; Nining Purwaningsih (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The use of curcuma and turmeric into rations as additives is expected to increase uprationsefficiencywith the resultthat increasing the growth rate of the quail. The use of curcuma andturmeric to the rations in the hope to improve the quality quail meat. This research used CompletelyRandomized Design (CRD) with 3 treatments and 6 replications. Each repeat consists of 5 pieces ofquail as a test unit. Treatment given in the form of a commercial ration (HI - PRO) added readyproducts of curcuma, turmeric, vitamins, minerals, and amino acids mixture. Treatments consisted ofconduct P1 (Rations = commercial rations + 0.0 %of curcuma and turmeric powder), P2 = commercialrations+ 1.0 % thecurcuma and turmericpowder) and P3 = commercial rations+ 2.0 % the curcumaand turmericpowder). Data was analyzed on the variance of the 5 % significantly, when there aresignificant differences, stated by orthogonal polynomial test. Variables observed are cooking loss, driploss and meat rotting test.The results showed that the granting of curcuma and turmeric in level 0.0; 0.1; and 2.0 % inthe commercial rations no significant (P > 0.05) for cooking loss and drip loss male quail meat.Conditions quail meat after 12 hourscutting all in a state of decay.